2009
DOI: 10.1002/mc.20558
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dichotomy between anchorage‐independent growth responses to bFGF and TPA reflects molecular switch in commitment to carcinogenesis

Abstract: We have investigated gene expression patterns underlying reversible and irreversible anchorage-independent growth (AIG) phenotypes to identify more sensitive markers of cell transformation for studies directed at interrogating carcinogenesis responses. In JB6 mouse epidermal cells, basic fibroblast growth factor (bFGF) induces an unusually efficient and reversible AIG response, relative to 12-O-tetradecanoyl phorbol-13-acetate (TPA)-induced AIG which is irreversible. The reversible and irreversible AIG phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…ERK oscillations might correlate with the regulation of an unidentified tumor suppressor activity. In support of this statement, bFGF regulates ERK oscillations and a reversible anchorage‐independent growth (AIG) response in JB6 mouse epidermal cells [1, 32]. How bFGF prevents acquisition of the malignant phenotype remains unknown, however, independent investigators have demonstrated that bFGF does not function as a tumor promoter alone or in combination with TPA in mouse skin [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…ERK oscillations might correlate with the regulation of an unidentified tumor suppressor activity. In support of this statement, bFGF regulates ERK oscillations and a reversible anchorage‐independent growth (AIG) response in JB6 mouse epidermal cells [1, 32]. How bFGF prevents acquisition of the malignant phenotype remains unknown, however, independent investigators have demonstrated that bFGF does not function as a tumor promoter alone or in combination with TPA in mouse skin [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…However, HLF can also transactivate c-JUN to promote tumor initiating cell-like properties of hepatoma cells by reactivating SRY-box transcription factor 2 and POU class 5 homeobox 1 (33). Ectopic HLF expression was shown to increase anchorage-independent growth and inhibit cell death in JB6 mouse epidermal cells (34). These observations raise the possibility that HLF may have different roles during tumorigenesis in a tissue-and context-specific manner.…”
Section: Discussionmentioning
confidence: 95%
“…14 We have defined gene expression patterns that are unique to bFGF in JB6 cells and not associated with the fully transformed JB6 phenotype (RT101 cells). 14 We have analyzed this data set and identified tumor suppressors unique to bFGF-dependent ERK oscillations (lysyl oxidase, 35 ≈7-fold ↑; aspartoacylase 2, 36 ≈9-fold ↑; insulin-like growth factor binding protein 5, 37 ≈9-fold ↑; and scavenger receptor class A, member 5, 38 ≈7-fold ↑). In human keratinocytes (Figure 2B), ERK oscillations were uniquely associated with increased tumor suppressor mRNA expression, including PDCD6, 39 CD44, 40 WNT7A, 41 HOPX, 42 WNT5A, 43 and others.…”
Section: Discussionmentioning
confidence: 99%
“…13 The mechanisms by which ERK oscillations are deregulated in vitro remain unclear; however, these observations suggest that the oscillating phenotype is under-represented in cell culture models used for toxicological investigations. ERK oscillations regulate a tumor suppressor activity that is conserved in vitro / in vivo , 14 suggesting that oscillatory behavior can significantly impact biological outcomes. Therefore, it is prudent to consider this regulatory feature in toxicological investigations, and there is a need to bridge the molecular dynamics observed in vitro with complex biology in tissues to improve the interpretation of experimental models used for hazard assessment and risk prediction.…”
Section: Introductionmentioning
confidence: 99%